2008
DOI: 10.1007/s11805-008-0079-2
|View full text |Cite
|
Sign up to set email alerts
|

Side effects during treatment of advanced gastric carcinoma by chemotherapy combined with CIK-cell transfusion in elderly people

Abstract: OBJECTIVE To study the side e ects and therapeutic results of autologous cytokine-induced killer (CIK) cell treatment in elderly patients with advanced gastric cancer. METHODSCIK cells were induced and cultured using biotechnics in vitro, and then the cells were infused back into the patients. Sixty elderly gastric cancer patients treated by chemotherapy (FOLFOX4 protocol) were followed-up. Among them, 29 patients were treated with CIK cells during application of chemotherapy. Short-term curative effects and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Another study that was published in 2008 focuses on the side effects occurring during CIK cell treatment [ 24 ]. Sixty elderly patients with advanced gastric cancer were treated with FOLFOX chemotherapy; 29 of them received additional intravenous (i.v.)…”
Section: Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Another study that was published in 2008 focuses on the side effects occurring during CIK cell treatment [ 24 ]. Sixty elderly patients with advanced gastric cancer were treated with FOLFOX chemotherapy; 29 of them received additional intravenous (i.v.)…”
Section: Gastric Cancermentioning
confidence: 99%
“…The twenty clinical studies discussed here prove CIK cell therapy to be an effective treatment option—after or along with conventional therapies—for patients with gastrointestinal tumors. In addition, as it was shown to be safe and not to induce major adverse effects, CIK cell therapy is a valuable alternative for patients not able or willing to tolerate side effects of conventional chemotherapy [ 24 , 33 ]. Within the different studies, CIK cells were applied either via peripheral veins, i.p., or via the common hepatic artery and all approaches were well tolerated.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Moreover, CIK cells can regulate and enhance immune function [16] . Studies have reported the level of tumor markers, change in cellular immune functions, exploration of molecule targets and a short-term efficacy in gastric cancer patients after chemotherapy plus CIK cells immunotherapy despite some side effects [17][18][19] . However, the relation between the frequencies of CIK cells immunotherapy and its clinical efficacy has not been examined.…”
Section: Introductionmentioning
confidence: 99%